Determinants of Breast Self-Examination (BSE) Practice Among Female Health Students at Sekolah Tinggi Kesehatan Indonesia Wirautama Bandung - Rais, Yulia; Ruhayati, Ratih; Framesti Cahyani, Andhia (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Breast cancer is the leading cause of cancer-related mortality among women in Indonesia. It accounts for 30.1% of all cancer cases in women, with 66,271 new cases and a mortality rate reaching 22,598 deaths. This high mortality rate is not only caused by the malignancy of the cancer cells themselves but also by the fact that more than 70% of patients present to health facilities at an advanced stage. Early detection through Breast Self-Examination (BSE) is a simple yet effective method; however, its practice remains low, even among health science students. Objective: This study aimed to analyze the determinants of BSE behavior, focusing on knowledge, attitudes, and exposure to information. Methods: This study employed an analytical quantitative method with a cross-sectional approach. Data were collected from health science students using validated questionnaires. Results and Discussion: The results showed a significant correlation between the level of knowledge and attitudes toward breast self-examination (BSE) practice. However, a knowledge-practice gap was identified, where high theoretical knowledge did not always translate into routine practice due to psychological barriers such as fear. Conclusion: Optimizing BSE behavior requires more than just knowledge; a more comprehensive approach is needed. Psychological support and digital-based educational strategies are essential to enhance self-efficacy among female students